2022
DOI: 10.1002/1348-9585.12326
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of occupational injuries among temporary agency worker and direct contract workers: Findings from the Korea Health Panel 2009–2018

Abstract: Objectives Several studies have reported health or safety risk of temporary agency workers (TAW). Since most of the studies are just cross‐sectional studies, we intended to identify the risk of occupational injury in TAW, using longitudinal study design. Methods The Korea Health Panel 2009–2018 data were used in the study. For the statistical analysis of this study, we used a panel logit model to identify the risk of occupational injury in TAW compared to direct contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…We observed in the present study that casual workers had about two times (AOR: 2.26, 95%CI: 1.04–4.92) increased odds of occupational injury compared to permanent workers. This is in agreement with earlier reports that casual workers are susceptible to an increased risk of occupational injuries compared to permanent workers [ 53 , 54 ]. In Ethiopia, a study among industrial workers reported that casual workers were about 7 times more likely to experience occupational injury compared to permanent workers [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed in the present study that casual workers had about two times (AOR: 2.26, 95%CI: 1.04–4.92) increased odds of occupational injury compared to permanent workers. This is in agreement with earlier reports that casual workers are susceptible to an increased risk of occupational injuries compared to permanent workers [ 53 , 54 ]. In Ethiopia, a study among industrial workers reported that casual workers were about 7 times more likely to experience occupational injury compared to permanent workers [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, unstable employment conditions are associated with low wages, poor working conditions, and weakened worker rights, leading to worsening health. 1 Workers with precarious employment have a high risk of accidents at work 2 ; a high frequency of harmful health behaviors, such as excessive drinking or smoking; and a lack of health care for prevention. 3 Therefore, nonstandard workers might have a relatively higher risk of unmet medical needs than standard workers.…”
Section: Introductionmentioning
confidence: 99%